Gestión administrativa y financiera y su incidencia en la rentabilidad de la cooperativa centro andino de acción popular CAAP., cantón Quevedo, año 2014 - Santana Salazar, Diana Carolina (2016)
This research was developed in the Andean Cooperative Action Center Popular CAAP. Which it is located in the Quevedo canton province of Los Rios. This consists of the administrative and financial management and its impact on the profitability of the Andean Cooperative Action Center Popular CAAP Quevedo Canton, 2014. Andean Cooperative Centre has extensive experience providing financial services it has been characterized as a responsible institution which seeks to establish mechanisms and standards to strengthen the soundness and stability of the financial system keeps. Currently the institution has a stable equilibrium, still was affected by failures in decision-making due to internal policies that handled affecting their administrative management, the goal is to boost financial services by analyzing the way in which It has structured the financial system of the company by strengthening existing shortcomings that have and training staff for the new management models where excellence is paramount in operations carried out by the organization suit. The proposal is an analysis generally to the efforts being carried out currently determining where weaknesses that may occur in the future as more serious threats affecting the financial stability of the institution, it is proposed to evaluate and plan activities are too They develop minutely controlling internal operations in a timely manner in order to improve them benefiting the company and customers.